Can a simple 'cost-awareness' campaign for laparoscopic hysterectomy change the use and costs of disposable surgical supplies? Pre–post non-controlled study. Issue 12 (11th December 2019) - Ross, Sue; Lier, Douglas; Mackinnon, Goldie; Bentz, Christine; Rakowski, Gloria; Capstick, Valerie A
Abstract : Objectives: Does a cost-awareness campaign for gynaecologists lead to a change in use and costs of disposable surgical supplies for laparoscopic hysterectomy (LH) without increasing hospital utilisation measures (operating room (OR) time or hospital length of stay (LOS))? Design: Pre–post non-controlled study. The OR database was used to identify relevant cases before and after the cost-awareness intervention, and provided information on quantity of each supply item, operative details and LOS. Setting: Lois Hole Hospital for Women, Edmonton, Alberta, Canada. Participants: 12 laparoscopic trained gynaecologists (7 female, 5 male) participated in both phases of the study. Eligible surgical cases were all LH cases for any indication for women aged ≥18 years. 201 cases were undertaken before the intervention (2011–2013) and 229 cases after the intervention (2016–2017). Intervention: The cost-awareness intervention for gynaecologists included site meetings and rounds providing information on costs of disposable and reusable instruments, a full day skills lab, OR posters about cost and effectiveness of disposable and reusable surgical supplies and demonstrations of reusable equipment (2015–2016). Primary outcome measure: Disposable supplies costs per case (standardised for 2016 unit costs). Results: There was a significant (p<0.05) reduction (unadjusted) in disposable supplies cost per case for LH between cases before and after the intervention: from $C1073, SD 281, to $C943 SD 209. Regression analysis found that the adjusted cost per case after the intervention was $C116 lower than before the intervention (95% CI −160 to −71). Neither OR time nor hospital LOS differed significantly between cohorts. Conclusions: Our study suggests that cost-awareness campaigns may be associated with reduction in the cost of surgery for LH. However, many other factors may have contributed to this cost reduction, possibly including other local initiatives to reduce costs and emerging evidence indicating lack of effectiveness of some surgical practices.